Magnetoelastic Stability of a Current-Carrying Rod in an External Magnetic Field - Kazarian, K.B. (Engineering Transactions, 1985)
A theoretical investigation of the effects of a longitudinal magnetic field upon the stability of a current-carrying rod is made. From general nonlinear equations of rod static equilibrium the linearised system of stability equations are obtained. It is showu that for all common boundary conditions the governing system equations are self-adjoint. By means of the stability static approach the critical values of Ampere force are obtained, beyond which the rod becomes unstable.